Influence of angiotensin-converting enzyme inhibitor ramipril on indicators of tubular kidney lesion in patients with chronic glomerulonephritis - Dolinna, M. O.; Svyntozelsky, O. O.; Долінна, Марія Олександрівна; Свинтозельський, Олександр Олексійович (My University, 2020)
To research and deepen the understanding of the links between morphological tubular kidney lesion parameters and serum markers – neutrophil gelatinase-associated lipocalin (NGAL) and interleukin-18 (IL-18), in patients with chronic glomerulonephritis (CGN) with saved renal function, as well as to estimate therapeutic correction of identified changes using ACE inhibitor ramipril. The diagnosis of “chronic glomerulonephritis” was verified based on clinical, laboratory and morphological data. Patients were divided into 2 clinical groups: patients with CGN and arterial hypertension (AH) and without AH. We used the data of renal biopsies to analyze the indicators of tubular kidney lesion in patients with CGN. Levels of serum NGAL and IL-18 were measured by means of ELISA kits. Treatment of patients was carried out over 24 weeks using the ACE inhibitor ramipril. The average daily dose of ramipril for the entire treatment period for patients with AH was 12.8±5.6 mg, patients of the second group – without AH, were treated with ramipril at a dose of 2.5 mg. On the basis of rank correlation analysis, we demonstrated that the level of serum NGAL is directly correlated with interstitial fibrosis (r=0.65; p<0.05), serum IL-18 – with dystrophic changes in the epithelium of renal tubules (r=0.81; p<0.05). Conclusion. Serum levels of NGAL and IL-18 are one of the most sensitive markers of tubular kidney lesion and have diagnostic efficiency up to 97%. A 24-week treatment with ACE inhibitor ramipril in patients with CGN with and without AH leads to a decrease in the levels of tubular kidney lesion markers.
Keywords: NGAL; IL-18; glomerulonephritis; diagnostics; ramipril